2006
DOI: 10.1101/lm.265906
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde amnesia in patients with hippocampal, medial temporal, temporal lobe, or frontal pathology

Abstract: There is considerable controversy concerning the theoretical basis of retrograde amnesia (R.A.). In the present paper, we compare medial temporal, medial plus lateral temporal, and frontal lesion patients on a new autobiographical memory task and measures of the more semantic aspects of memory (famous faces and news events). Only those patients with damage extending beyond the medial temporal cortex into the lateral temporal regions showed severe impairment on free recall remote memory tasks, and this held for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 64 publications
(97 reference statements)
1
77
0
Order By: Relevance
“…In addition, remote autobiographical memory was substantially impaired in three other patients, who had damage to one or more cortical areas including the lateral temporal and frontal lobes (Bayley et al, 2005b). Others have also emphasized the importance of lateral temporal and frontal lobe pathology for understanding impaired remote autobiographical memory (Eslinger, 1998;Kapur, 1999;Kopelman et al, 1999;Bright et al, 2006). There is a need for thorough, quantitative anatomical information for all the patients being studied.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, remote autobiographical memory was substantially impaired in three other patients, who had damage to one or more cortical areas including the lateral temporal and frontal lobes (Bayley et al, 2005b). Others have also emphasized the importance of lateral temporal and frontal lobe pathology for understanding impaired remote autobiographical memory (Eslinger, 1998;Kapur, 1999;Kopelman et al, 1999;Bright et al, 2006). There is a need for thorough, quantitative anatomical information for all the patients being studied.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the available group studies, which come from three different laboratories (11,12,20), have found that remote autobiographical memory is intact when damage is limited to the medial temporal lobe and that impaired autobiographical memory is associated with lateral temporal or frontal lobe pathology.…”
Section: Discussionmentioning
confidence: 99%
“…One approach has been to use a simple, standardized test like the Autobiographical Memory Interview (9), which asks three questions about each of three different past time periods. Using this test, or a modified version of it, a number of studies have found remote memory to be intact after damage limited to the medial temporal lobe (7,(10)(11)(12)). Yet, a few single-case studies have found remote memory to be impaired (refs.…”
mentioning
confidence: 99%
“…The effects of subcortical lesions were contrasted with those of selective cortical lesions, because widespread damage limited to cortex may cause relatively greater deficits in retention of preoperatively acquired information than new learning (Thornton et al, 1997;Bright et al, 2006;Browning and Gaffan, 2008). We considered the entorhinal cortex (ERh), because it is unambiguously part of the putative medial temporal lobe memory system (Squire and Zola-Morgan, 1991), yet its involvement in retention and new learning remains unclear, largely because studies in monkeys typically also damage the perirhinal cortex (Leonard et al, 1995;Meunier et al, 1996;Charles et al, 2004).…”
Section: Introductionmentioning
confidence: 99%